2020
DOI: 10.1111/cobi.13500
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental insights on when social network data are most critical for conservation planning

Abstract: As declines in biodiversity accelerate, there is an urgent imperative to ensure that every dollar spent on conservation counts toward species protection. Systematic conservation planning is a widely used approach to achieve this, but there is growing concern that it must better integrate the human social dimensions of conservation to be effective. Yet, fundamental insights about when social data are most critical to inform conservation planning decisions are lacking. To address this problem, we derived novel p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…This agrees with Pham et al (2015) who revealed that consultations ought to be conducted before implementing conservation projects. The findings are further in agreement with Rhodes et al (2020), who asserted that the participation of various stakeholders is essential as they are most conversant with forest management issues. Moreover, Dobrynin et al (2020) stated that effective collaborative forest management standards require consultations with local communities and indigenous people and mechanisms for resolving grievances.…”
Section: They Don't Allow Us To Patrol Areas Where They Know That The...supporting
confidence: 89%
See 2 more Smart Citations
“…This agrees with Pham et al (2015) who revealed that consultations ought to be conducted before implementing conservation projects. The findings are further in agreement with Rhodes et al (2020), who asserted that the participation of various stakeholders is essential as they are most conversant with forest management issues. Moreover, Dobrynin et al (2020) stated that effective collaborative forest management standards require consultations with local communities and indigenous people and mechanisms for resolving grievances.…”
Section: They Don't Allow Us To Patrol Areas Where They Know That The...supporting
confidence: 89%
“…This is contrary to the Charlene et al ( 2017) study, which showed that most community members who depended on forests were not offered a platform to contribute to forest management or action plan development. However, scholars (Rhodes et al, 2020;Zhang et al, 2020) opined that integrating opinions from local communities in conservation planning and development is an essential aspect of sustainable forest conservation. Lise (2009) consistently argued that effective community participation remains a mirage if community members are not involved in planning, implementation, monitoring, and evaluation processes.…”
Section: Community Participation In Cfm Meetings For Forest Conservationmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach may be valuable for refining large-scale interventions; in our case, this approach is cost-effective if a large number of villages are included in the intervention (although the absolute cost of data collection is still low). Simple value of information analyses combined with simulations can help to guide these decisions (Rhodes et al, 2020;Akbarpour, Malladi & Saberi, 2020;Canessa et al, 2015). Third, the large literature on network interventions (Valente, 2012) suggests improvements to intervention design that apply across contexts, such as the use of clustered targeting strategies (Centola, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…[3], we argue that important information can be missed in ecosystem service studies that analyze only social or ecological networks rather than an integrated SEN [19,86,87], such as the role of social relationships in shaping management actions that affect the ecological network [88,89] or the complex ecological interactions underlying ecosystem service supply [5]. SENs can complement other integrated modeling frameworks (e.g., [90,91]) that acknowledge linkages between, and complexities within, both social and ecological layers.…”
Section: ****** Box 1 How Can Sens Complement Other Approaches To Eco...mentioning
confidence: 99%